Cutaneous Indeterminate Cell Histiocytosis of Donor Origin After Allogeneic Hematopoietic Stem-Cell Transplantation. (September 2017) - Santos-Briz, Angel; Román, Concepción; Corral, Rocío; de Dios, Alvaro; Vázquez, Lourdes; Ludeña, María D.
Abstract : Abstract: Allogeneic hematopoietic stem-cell transplantation and solid-organ transplantation are associated with an increased risk of secondary neoplasms. Indeterminate cell histiocytosis (ICH) is a rare disease composed of so-called indeterminate cells, an alleged cutaneous dendritic cell subset displaying histological and some ultrastructural and immunophenotypic features of Langerhans cells but lacking Birbeck granules. We report a case of cutaneous ICH occurring after allogeneic hematopoietic stem-cell transplantation for a myelodysplastic syndrome in a 56-year-old man. Microsatellite analysis demonstrated that the neoplastic cells were derived from the donor's hematopoietic system. This case broadens the spectrum of complications after stem-cell transplantation and demonstrates that cutaneous ICH in the setting of myelodysplastic syndromes may have a nonrelated origin to dysplastic myeloid cells.